1,5,7-Triazabicylodec-5-ene-Promoted Direct Vinylogous Aldol Reaction for the Synthesis of 3-Hydroxy-2-oxoindole Derivatives - Zhang, Xianhui; Zhou, Li; Mahmood, Qaiser; Zhao, Mengmeng; Wang, Xiaowu; Wang, Qinggang (Synlett, 2019)
A simple and efficient method has been developed for the synthesis of 3-hydroxy-2-oxoindole derivatives through a direct vinylogous aldol reaction of allylic esters with isatins, catalyzed by 1,5,7-triazabicyclodec-5-ene. This method affords a variety of 3-hydroxy-2-oxoindole derivatives in moderate to excellent yields with high regioselectivities. An asymmetric version of this reaction catalyzed by Corey’s chiral guanidine proceeded with moderate enantioselectivity. The protocol can also be used to synthesize isatin spiro ethers.
Keywords: hydroxyoxoindoles; vinylogous aldol reaction; triazabicyclododecene; isatins; isatin spiro ethers; asymmetric catalysis